PENGHARGAAN DIRI DAN PENALARAN MATEMATIS SISWA MTS - Nur Sholihat, Nasution Annisa; Hidayat, Wahyu; Rohaeti, Euis Eti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to analyze and examine in depth about the ability of mathematical reasoning that is influenced by self-esteem of MTs students. The method in this research using correlational method with quantitative approach. The population in this study were students of MTs in Kota Cimahi and the samples were 20 people determined by purposive sampling technique in one of MTs in Cimahi City. Instrument in this research is test of critical thinking ability of mathematic as much as 5 item and scale of student self confidence as 30 scale statement. The results of this study concluded that the mathematical reasoning ability of students of MTs is positively influenced by their self-esteem of 52.5%, while 47.5% is influenced by factors other than self-esteem students